Pengaruh Tingkat Pendidikan dan Investasi PMDN Terhadap Produktivitas Tenaga Kerja di Provinsi Sumatera Barat - Angraini, Nidia; Ritonga, Mentari (Jurnal Salingka Nagari, 2024)
One of the most crucial measures of economic development is labour productivity. The economy needs to increase labour productivity to remain globally competitive. The ability to perform a task well is known as labour productivity, and practical work can boost regional output. In the long run, this productivity is also considered a key factor in expanding the national economy. GRDP and the number of employees in an economic sector can be compared to determine the level of labour productivity. This study aims to partially and simultaneously examine the effects of health, education, and PMDN investment on labour productivity in West Sumatra between 2018 and 2022. Panel data regression is used in this study. This study uses time series data covering a cross-section of West Sumatra Province's cities and regencies from 2018 to 2022. The regression analysis results showed that both PMDN investment and educational attainment influenced labour productivity. On the other hand, labour productivity was positively and marginally impacted by PMDN investment and educational attainment.